PHARMACOGNOSTICAL AND PHYSICOCHEMICAL EVALUATION OF THE PLANT LEUCAS ASPERA - Kripa Kg; Sangeetha R; Chamundeeswari D (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Leucas aspera (Willd.) Linn. is a herbaceous annual distributed throughout India from the Himalayas down to Ceylon. This study was aimed to investigate the pharmacognostical, phytochemical characteristics, and heavy metal content of the aerial parts of L. aspera. Methods: The aerial parts of the plant were subjected to macroscopical and microscopical characterization, followed by physicochemical evaluations using standardized procedures. Atomic absorption spectroscopy (AAS) of the dried plant powder was done to determine the metal and mineral content. Preliminary phytochemical screening and metabolite analysis of the hydroalcoholic extract of L. aspera (HAELA) were also performed to analyze the various phytoconstituents. Results: In this study, the microscopic characteristics of L. aspera were found to be consistent with earlier reports. The total ash value was relatively high (11.5% w/w). Alcohol soluble and water-soluble extractive values were found to be 6.5% and 9%, respectively. AAS indicated the plant to contain insignificant quantities of heavy metals and considerable amounts of copper, sodium, potassium, and iron. Phytochemical analysis revealed the presence of alkaloids, flavonoids, glycosides, lignins, phenols, saponins, sterols, and tannins in HAELA. Conclusion: The pharmacognosy - anatomical, physicochemical, heavy metal characteristics, and the preliminary phytochemical studies of the aerial parts of L. aspera have revealed the presence of phytoconstituents such as triterpenoids, phenolic compounds, flavonoids, and glycosides; insignificant quantities of heavy metals and significant content of phenolics and tannins in the plant. Keywords: Leucas aspera, Ash value, Heavy metal content, Atomic absorption spectroscopy.